Mobile application for an electronic device - Vieira, Hélder Francisco Silva (2018)
This project aims the development of a mobile app used to control and monitor an ultra low power electronic device through a smartphone (phone or tablet). The electronic device collects, periodically and autonomously, data of the surround environment, like temperature and humidity. The smartphone is used as a cheap solution to access the electronic device, to get the data stored on it, to show the data in a graphical way (based on charts) for local validation, to contextualize geographically and temporally the collected data and also to submit the data to the cloud (web server). The communication between electronic device and smartphone is done using, as wireless communication technology, the Bluetooth Low Energy (BLE), which is available in almost all smartphones. Whenever the app picks the data from the electronic devices, it also determines the geographical location and the time of the picking process, using the resources available in the smartphone. The geographical location is obtained from the GPS coordinates or, alternatively, from wireless and/or GSM access points. The web server is used as a global repository to store the data obtained by the several smartphones from the electronic devices. This way, it is possible to use more advanced data analysis solutions to tracking the contexts where the devices were used. This generic solution could be used to tracking objects, animals and even persons, namely in industrial and shipping processes. For the development of this app were defined four main requirements: use Apache Cordova Cordova technology to implement the app to distinct mobile platforms (Android, iOS, Windows Mobile, etc.) using a single development project; use BLE wireless technology to communicate with the electronic device; conceive and build a simple and easy to use interface; send the collected data to a web server through restfull services.